Stem cell biology of myelodysplastic syndrome: preliminary findings from Sri Lankan studies and their diagnostic and therapeutic implications - Goonasekara, H.W.W. (Faculty of Medicine, University of Colombo, 2020)
Myelodysplastic syndrome (MDS) is a phenotypically heterogeneous bone marrow haematopoietic stem cell (BM-HSC) ...
Keywords: Myelodysplastic syndrome; Biology; Sri Lanka